Digital Discourse Analysis of the Spread of Disinformation on TikTok Social Media - Devina Sianturi; Melyana Pinem; Naomi Pricillia Tarigan; Miko Parsaoran Simanjuntak (Student Scientific Creativity Journal, 2026)
based information consumption and the low level of verification practices among young users. This condition has serious implications for the formation of public perception, digital literacy, and social dynamics within society. This study aims to gain an in-depth understanding of how disinformation is constructed, experienced, and interpreted by TikTok users in their daily lives. This research employs a qualitative approach using digital discourse analysis based on a critical perspective, focusing on subjective experiences and social processes in digital interactions. Data were collected through in-depth interviews, observation of TikTok content, and analysis of digital documents, involving 12–15 active TikTok users aged 18–30 years. Data analysis was conducted using reflective thematic analysis to identify patterns of meaning emerging from participants’ experiences. The findings reveal three main themes: instant trust shaped by visual and emotional resonance, delayed doubt due to the rapid rhythm of digital consumption, and the negotiation of meaning in online social interactions. These results indicate that disinformation operates not merely as a distortion of information but as a complex socio-affective experience. Theoretically, this study enriches the integration of critical discourse analysis, digital discourse, and audience reception theory. Practically, the findings provide implications for strengthening digital literacy, developing communication policies, and designing more contextual educational interventions. Furthermore, this research opens opportunities for further exploration of user experience dynamics within the ever-evolving social media ecosystem.